2023
DOI: 10.3390/knowledge3010003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Evaluation Method in the Field of University Education: Application to a Course on Energy Markets

Abstract: The Bologna Plan adopted by European universities ended the hegemony of an evaluation system exclusively based on the performance of traditional examinations. In this area, with a view to revitalizing grading models in university education, a wide range of evaluation mechanisms has been developed in recent years. Using them, teachers may evaluate the learning levels of their students, including both the specific competences of the taught subject and the transversal competences that help students further develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study covering the period from 2005 to 2016 showed that the most common individual approach to assessing the quality of service of a website and its choice is AHP (the analytic hierarchy process) and the main criterion for its performance is responsiveness [18]. Moreover, multi-criteria decision-making models help in evaluating environmental education programs [19], the effectiveness of e-learning (e-learning) [20], and even in evaluating acquired knowledge, abilities, and actitudes at the Energy Markets course [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study covering the period from 2005 to 2016 showed that the most common individual approach to assessing the quality of service of a website and its choice is AHP (the analytic hierarchy process) and the main criterion for its performance is responsiveness [18]. Moreover, multi-criteria decision-making models help in evaluating environmental education programs [19], the effectiveness of e-learning (e-learning) [20], and even in evaluating acquired knowledge, abilities, and actitudes at the Energy Markets course [21].…”
Section: Literature Reviewmentioning
confidence: 99%